Perancangan Dokumen SNI ISO 17025:2017 untuk Laboratorium Beton dan Konstruksi di Universitas Kristen Petra - Karmila Shieny Gunawan; Jani Rahardjo (Jurnal Titra, 2022)
Concrete and Construction Laboratory of Petra Christian University (PCU) is one of the testing laboratories under the auspices of the Civil Engineering study program and faculty of Civil Engineering and Planning. Design of SNI ISO 17025:2017 document is required for the Concrete and Construction Laboratory of PCU to obtain accreditation in order that the concrete test results can be recognized internationally. This research was conducted by identifying business processes, conducting initial and final document gap analysis, document creation, and document verification. The results of the initial document gap analysis show that the percentage of document completeness that the laboratory has is 8,74% with a total of four documents. Document creation is done by designing and creating documents that are not yet available as well as making adjustments to the documents that are already available. After the documents have been created and verified, the results of final document gap analysis show that the percentage of document completeness has increased to 80,60% with a total of 59 documents. The increase in the document completeness through the results of the initial and final document gap analysis was 71,86%.